The risk implications of insurance securitization: The case of catastrophe bonds - Hagendorff, Bjoern; Hagendorff, Jens; Keasey, Kevin; Gonzalez, Angelica (Journal of Corporate Finance, 2014)
Catastrophe (Cat) bonds are insurance securitization vehicles which are supposed to transfer catastrophe-related underwriting risk from issuers to capital markets. This paper addresses key, unanswered questions concerning Cat bonds and offers the following results. First, our findings show firms that issue Cat bonds exhibit less risky underwriting portfolios with less exposure to catastrophe risks and overall less need to hedge catastrophe risk. These results show that the access to the market for insurance securitization is easiest for firms with less risky portfolios. Second, firms that issue Cat bonds are found to experience a reduction in their default risk relative to non-issuing firms and our results, therefore, demonstrate that Cat bonds provide effective catastrophe hedging for issuing firms. Third, firms with less catastrophe exposure, increase their catastrophe exposure following an issue. Therefore, our paper cautions that the ability to hedge catastrophe risk causes some firms to seek additional catastrophe risk.